2016
DOI: 10.1080/0167482x.2016.1216960
|View full text |Cite
|
Sign up to set email alerts
|

Negative impressions of childbirth in a North-West England student population

Abstract: Negative Impressions of Childbirth in a North-West England Student Population ABSTRACTBackground: Socio-cultural childbirth representations can influence perceptions of childbirth

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 40 publications
1
20
0
4
Order By: Relevance
“…Vicarious exposure to negative birth information, often referred to as "birth horror stories," has been highlighted elsewhere as an important determinant of FOC in nulliparous and primiparous women (Stoll, Hall, Janssen, & Carty, 2014;Thomson, Stoll, Downe, & Hall, 2016). One source of information, media representation, has been subject to debate (Hundley, Duff, Dewberry, Luce, & Van Teijlingen, 2014).…”
Section: Moderators Of Women's Fearsmentioning
confidence: 99%
“…Vicarious exposure to negative birth information, often referred to as "birth horror stories," has been highlighted elsewhere as an important determinant of FOC in nulliparous and primiparous women (Stoll, Hall, Janssen, & Carty, 2014;Thomson, Stoll, Downe, & Hall, 2016). One source of information, media representation, has been subject to debate (Hundley, Duff, Dewberry, Luce, & Van Teijlingen, 2014).…”
Section: Moderators Of Women's Fearsmentioning
confidence: 99%
“…Negative impressions of birth conveyed by family and friends were also linked to higher fear scores, whereas witnessing a birth firsthand was associated with lower fear. 7,12 These findings point to the importance of reevaluating how young people learn about birth to counteract negative or exaggerated media portrayals and negative birth stories. Children and youths should be given opportunities to learn about and ask questions about pregnancy and birth early on.…”
Section: Discussionmentioning
confidence: 98%
“…Several studies have investigated maternity care preferences and attitudes of young women and men who plan to have children in the future . These studies typically focus on attitudes of young people in a single country or region.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Public discourses about birth and the sharing of positive and negative birth experiences mould women's perceptions of what constitutes a "natural," "normal" or "risky" birth process and condition their expectations (Thomson et al 2017). Research has also shown that severe fear of childbirth may increase the possibility of caesareans (Fenaroli et al 2016;Ryding et al 2015) as women become afraid of birthing their own babies physiologically (Kay 2016) and prefer to give way to the "authoritative knowledge" (Jordan 1993(Jordan [1978) of the medical profession.…”
Section: Fear Risk and Authoritative Knowledgementioning
confidence: 99%